The parasitic worm product ES-62 protects the osteoimmunology axis in a mouse model of obesity-accelerated ageing - Harnett, Margaret M.; Doonan, James; Lumb, Felicity E.; Crowe, Jenny; Damink, Roel Olde; Buitrago, Geraldine; Duncombe-Moore, Josephine; Wilkinson, Debbie I.; Suckling, Colin J.; Selman, Colin; Harnett, William (Frontiers in Immunology, 2022)
Despite significant increases in human lifespan over the last century, adoption of high calorie diets (HCD) has driven global increases in type-2 diabetes, obesity and cardiovascular disease, disorders precluding corresponding improvements in healthspan. Reflecting that such conditions are associated with chronic systemic inflammation, evidence is emerging that infection with parasitic helminths might protect against obesity-accelerated ageing, by virtue of their evolution of survival-promoting anti-inflammatory molecules. Indeed, ES-62, an anti-inflammatory secreted product of the filarial nematode Acanthocheilonema viteae, improves the healthspan of both male and female C57BL/6J mice undergoing obesity-accelerated ageing and also extends median lifespan in male animals, by positively impacting on inflammatory, adipose metabolic and gut microbiome parameters of ageing. We therefore explored whether ES-62 affects the osteoimmunology axis that integrates environmental signals, such as diet and the gut microbiome to homeostatically regulate haematopoiesis and training of immune responses, which become dysregulated during (obesity-accelerated) ageing. Of note, we find sexual dimorphisms in the decline in bone health, and associated dysregulation of haematopoiesis and consequent peripheral immune responses, during obesity-accelerated ageing, highlighting the importance of developing sex-specific anti-ageing strategies. Related to this, ES-62 protects trabecular bone structure, maintaining bone marrow (BM) niches that counter the ageing-associated decline in haematopoietic stem cell (HSC) functionality highlighted by a bias towards myeloid lineages, in male but not female, HCD-fed mice. This is evidenced by the ability of ES-62 to suppress the adipocyte and megakaryocyte bias and correspondingly promote increases in B lymphocytes in the BM. Furthermore, the consequent prevention of ageing-associated myeloid/lymphoid skewing is associated with reduced accumulation of inflammatory CD11c+ macrophages and IL-1 in adipose tissue, disrupting the perpetuation of inflammation-driven dysregulation of haematopoiesis during obesity-accelerated ageing in male HCD-fed mice. Finally, we report the ability of small drug-like molecule analogues of ES-62 to mimic some of its key actions, particularly in strongly protecting trabecular bone structure, highlighting the translational potential of these studies.